Antinociceptive effects of purified Curcuma longa in mice - Sharma, Ashish; Rauniar, Gajendra Prasad (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Since ancient times Curcuma longa is said to have antinociceptive effects in literature. Methods: It was a quantitative experimental study done in the laboratory setting of the department of Clinical Pharmacology and Therapeutics, BP Koirala Institute of Medical Sciences, Dharan, Nepal (BPKIHS). Hot plate test, Tail flick test and Writhing test were used for evaluating the antinociceptive effects. Animals were divided into five groups of six each, group I as control, group II as standard control whereas groups III, IV and V as test groups (three doses). Control and the three test drug doses were given for 21 days. Data were presented as mean ±Standard Error of Mean. Statistical differences between the test drug and control groups as well as within the test drug groups were calculated using Mann-Whitney U test. A probability level less than 0.05 (p < 0.05) was considered significant. Results: Significant effects in comparison to vehicle were observed in all the three anti nociceptive test models at 200mg /kg test dose of aqueous extract of purified Curcuma longa (CL). No significant effect as compared to vehicle was observed at 50mg/kg and 100 mg/kg test doses of CL. Conclusions: This study showed that CL possesses antinociceptive effect. The mechanism(s) and active principle(s) behind the effects of CL could not be established.